O material manipulável no ensino e aprendizagem das noções básicas de geometria analítica a um aluno com cegueira - CARDOSO, Lucélia Valda de Matos (Universidade Federal do Pará, 2021)
The present study aimed to investigate the use of manipulative material (built together with the student) as a resource to the teaching-learning process in Basics of Analytical Geometry to a student with acquired blindness. A part of the research (application of the activities) took place in 4 months and consisted of a period of observation, application of interviews and verification of the content worked. The research had the qualitative approach and used as a methodology the case study, in each developed activity, we propose problems that were solved with the aid of the manipulable material, in order to understand what the contributions of this resource to the process of teaching and learning the Basics of Analytical Geometry to students with blindness. In this sense, the research is being developed in a public school established in Mosqueiro (district of Belém / PA) in the neighborhood of Carananduba, involving only a blind student of the third year of high school, night shift. The results obtained by the research demonstrated that the use of the manipulative material contributed to the learning and understanding of the mathematical concepts of the Basics of Analytical Geometry after familiarization with the manipulable material. Thus, the analysis of the data showed that there was a significant contribution in the understanding of the mathematical concepts, which was provided by the strengthening of the interaction and the construction of the manipulable material.